2021
DOI: 10.1055/s-0040-1721017
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Music on Neurosurgical Cases: A Neglected Knowledge

Abstract: Background The human brain can respond to and participate in music. Learning to play a musical instrument requires complex multimodal skills involving the simultaneous perception of several sensory modalities. In case of brain damage, the musician and nonmusician brains may have different capacities for reorganization and neural remapping. We aimed to investigate the effect of music on patients who had a brain tumor and/or underwent a neurosurgical procedure, comparing the recovery of those who had a musical b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

4
5

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 55 publications
0
11
0
Order By: Relevance
“…According to the study performed by it was evaluated that the music particularly classical music is found to serve as source of diverting the attention of thoughts from an unpleasant Music serves as an effective source reducing panic attacks, stress and depression among the patients in preoperative and postoperative stages as well. The patients who are provided with Mozart's therapy were observed to express lower blood pressures, pulse rate and anxiety, during the hospital stays (Gasenzer, Kanat & Nakamura, 2021). It can be observed through clinical evidence that music is also used recently in the antenatal clinics as it is one of the effective methods of increasing the heart rate among fetus, promoting good health and cognition.…”
Section: Mozart's Music Effectsmentioning
confidence: 99%
“…According to the study performed by it was evaluated that the music particularly classical music is found to serve as source of diverting the attention of thoughts from an unpleasant Music serves as an effective source reducing panic attacks, stress and depression among the patients in preoperative and postoperative stages as well. The patients who are provided with Mozart's therapy were observed to express lower blood pressures, pulse rate and anxiety, during the hospital stays (Gasenzer, Kanat & Nakamura, 2021). It can be observed through clinical evidence that music is also used recently in the antenatal clinics as it is one of the effective methods of increasing the heart rate among fetus, promoting good health and cognition.…”
Section: Mozart's Music Effectsmentioning
confidence: 99%
“…Limitation: A comprehensive understanding of the pathophysiology is crucial in neurosurgical practice (28). For that reason, experimental studies are important, because cellular changes and the morphological mechanisms leading to the pathology can only be seen in animal studies (29), so histopathological basis and mechanism(s) of neurogenic pulmonary edema after SAH can only be detected by experimental studies.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…It is a known disease from ancient times (8), but it is currently a common clinical problem in neurosurgical practice (9), (10). A comprehensive understanding of pathophysiology is an important issue in medical practice (11), (12). Alcohol has complex effects on the brain tissue.…”
Section: Accepted Manuscriptmentioning
confidence: 99%